Planning for a pandemic: Mitigating risk to radiation therapy service delivery in the COVID‐19 era. Issue 3 (22nd June 2020) - Anderson, Nigel; Thompson, Kenton; Andrews, Judy; Chesson, Brent; Cray, Alison; Phillips, Damien; Ryan, Michelle; Soteriou, Sally; Trainor, Glenn; Touma, Nilgun
Abstract: The novel coronavirus (COVID‐19) has rapidly impacted all of our lives following its escalation to pandemic status on 11 March 2020. Government guidelines and restrictions implemented to mitigate the risk of COVID‐19 community transmission have forced radiation therapy departments to promptly adjust to the significant impact on our ability to deliver best clinical care. The inherent nature of our tri‐partied professions relies heavily on multidisciplinary teamwork and patient–clinician interactions. Teamwork and patient interaction are critical to the role of a radiation therapist. The aim of this paper is to describe the experience of the Peter MacCallum Cancer Centre's (Peter Mac) radiation therapy services during the preliminary stages of the COVID‐19 pandemic in minimising risk to patients, staff and our clinical service. Four critical areas were identified in developing risk mitigation strategies across our service: (a) Workforce planning, (b) Workforce communication, (c) Patient safety and wellbeing, and (d) Staff safety and wellbeing. Each of these initiatives had a focus on continuum of clinical care, whilst minimising risk of cross infection for our radiation therapy workforce and patients alike. Initiatives included, but were not limited to, establishing COVID‐Eclipse clinical protocols, remote access to local applications, implementation of Microsoft Teams, personal protective equipment (PPE) guidelines and virtual 'Division of Radiation Oncology' briefing/updates. The COVID‐19 pandemic has dictated change in conventional radiation therapy practice. It is hoped that by sharing our experiences, the radiation therapy profession will continue to learn, adapt and navigate this period together, to ensure optimal outcomes for ourselves and our patients. Abstract : This commentary describes the operational changes made by the Peter MacCallum Cancer Centre's Radiation Therapy Services during the initial stages of the COVID‐19 pandemic. Changes to clinical operations, to ensure optimal patient and staff safety and wellbeing, whilst maintaining a high‐ quality clinical service, are detailed.